2021
DOI: 10.3390/nano11020284
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Red-Enhanced and Biocompatible Upconversion Nanoparticles

Abstract: The exceptional optical properties of lanthanide-doped upconversion nanoparticles (UCNPs) make them among the best fluorescent markers for many promising bioapplications. To fully utilize the unique advantages of the UCNPs for bioapplications, recent significant efforts have been put into improving the brightness of small UCNPs crystals by optimizing dopant concentrations and utilizing the addition of inert shells to avoid surface quenching effects. In this work, we engineered bright and small size upconversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…The in vitro cytotoxicity evaluation of the loaded drugs, nifedipine, atorvastatin calcium, and their combination (in a 1:1 ratio) was conducted using the MTS assay, following a modified method of Alkahtani et al [26]. The MTS reagent (cell Titer 96 ® Aqueous one solution cell proliferation Assay) was supplied by Promega (Southampton, UK).…”
Section: In Vitro Cytotoxicity Assessment Of Nifedipine and Atorvasta...mentioning
confidence: 99%
“…The in vitro cytotoxicity evaluation of the loaded drugs, nifedipine, atorvastatin calcium, and their combination (in a 1:1 ratio) was conducted using the MTS assay, following a modified method of Alkahtani et al [26]. The MTS reagent (cell Titer 96 ® Aqueous one solution cell proliferation Assay) was supplied by Promega (Southampton, UK).…”
Section: In Vitro Cytotoxicity Assessment Of Nifedipine and Atorvasta...mentioning
confidence: 99%
“…Therefore, we found that phagocytic cells (such as monocytes and dendritic cells) had higher affinity to the UCNPs than the other nonphagocytic cells. In addition, PG clustering algorithms were used to identify sub-cell types of monocytes and dendritic cells, which is sub-divided into 3 clusters (PG#1, 4, 18) and 4 clusters (PG#2, 3,19,27), respectively. Our study demonstrated a new technical framework to understand the heterogeneous interactions of conventional nanomaterials with complex human immune cells, which will be helpful for the safe use of nanomaterials in biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cytotoxicity investigations of UCNPs were typically carried out using simple assays, such as MTT and MTS assays in vitro at the cellular level. [27][28][29] Moreover, the data obtained from the evaluation of homogenous singlecell types are insufficient, and may even cause misconceptions of the NPs toxicity assessment. To address this, extensive toxicity assessments in heterogeneous cell types may contribute to more complete knowledge of the UCNPs cytotoxicity and nano-safety assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide-doped upconversion nanoparticles (UCNPs) have recently attracted special interest in numerous interesting applications. Their ability to upconvert one or more low-energy NIR photons to one high-energy visible photon, as well as their photostability and photoluminescence tunability, opens the door for advanced and promising applications [1][2][3][4][5]. These include bio-applications, quantum sensing, optoelectronics, superresolution microscopy, and renewable energy [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%